Spectroscopic investigation, molecular orbital studies, frequency and solvent dependent NLO properties of (2E)-1-(4-bromophenyl)-3-phenylprop-2-en-1-one. (10th November 2019) - Balachandran, V.; Anitha, K.; Narayana, B.; Karunanidhi, M.; Revathi, B.
ABSTRACT: The structure and the vibrational frequencies of the fundamental modes of the optimized geometry of (2E)-1-(4-bromophenyl)-3-phenylprop-2-en-1-one (BP3PP) have been determined. A detailed vibrational spectral analysis was carried out and the assignments of the observed bands have been proposed on the basis of potential energy distribution (PED). The UV-Vis spectral analysis has been performed by the TD – DFT method at the CAM-B3LYP/6–31 + G (d) level in gas phase and different solvent phase. Other molecular properties such as ionization energy, electron affinity, chemical potential, global hardness and electrophilicity were also calculated. The static and dynamic (frequency) average polarizability ( α ), first- and second- order hyperpolarizabilities ( β and γ ) have been investigated by using the CAM-B3LYP method. The solvent effects on the polarizability ( α ), first- and second- order hyperpolarizabilities ( β and γ ) have also been evaluated by IEFPCM model. The results display significant second- and third-order molecular nonlinearity of the title compound.